Studies Comparison of Health Promotion between Leaflets with Videos on Knowledge About Cancer Breast - Pertiwi, Rina; Herawati, Netti (Program Magister Teknologi Pendidikan Universitas Jambi, 2016)
This study aims to determine the ratio of health promotion to knowledge about breast Cancer and breasts Cancer early detection skills (BE AWARE) in adolescent girls at Jatiling Jambi Health Polytechnic Year 2016. This type of research is quasi experimental with non-randomized pre-test-post-test group design. Instruments used are Instruments test knowledge about breast cancer and test instruments BSE skills. Data analysis was performed multivariate (MANOVA) and paired samples T-Test and independent samples T-Test. The results of the study were (1) there was a difference in knowledge about breast cancer between the groups that were given health promotion using leaflets with the group that was given health promotion using video, video media is better and gives more dominant influence to the knowledge aspects of breast cancer. Differences in breast cancer early detection skills (BSE) between health-promoted groups used leaflets and health-promoted groups used better videos media and more dominant influence on aspect of girls' breasts self- examination. Based on the results of the study, it was concluded that the use of videos US a media of health promotion is better than the use of leaflets to increase knowledge about breasts cancer and girls skills in early detection of breast cancer, so educators can make the video as an alternatives tools in providing learning to students.